DNA functionalization by dynamic chemistry - Kanlidere, Zeynep; Jochim, Oleg; Cal, Marta; Diederichsen, Ulf (Beilstein Journal of Organic Chemistry, 2016)
Dynamic combinatorial chemistry (DCC) is an attractive method to efficiently generate libraries of molecules from simpler building blocks by reversible reactions under thermodynamic control. Here we focus on the chemical modification of DNA oligonucleotides with acyclic diol linkers and demonstrate their potential for the deoxyribonucleic acid functionalization and generation of libraries of reversibly interconverting building blocks. The syntheses of phosphoramidite building blocks derived from D-threoninol are presented in two variants with protected amino or thiol groups. The threoninol building blocks were successfully incorporated via automated solid-phase synthesis into 13mer oligonucleotides. The amino group containing phosphoramidite was used together with complementary single-strand DNA templates that influenced the Watson–Crick base-pairing equilibrium in the mixture with a set of aldehyde modified nucleobases. A significant fraction of all possible base-pair mismatches was obtained, whereas, the highest selectivity (over 80%) was found for the guanine aldehyde templated by the complementary cytosine containing DNA. The elevated occurrence of mismatches can be explained by increased backbone plasticity derived from the linear threoninol building block as a cyclic deoxyribose analogue.
Keywords: base-pairing; base-pair mismatch; DNA functionalization; DNA templates; dynamic combinatorial chemistry; D-threoninol based scaffolds